Intersentential Anaphoric Use of Personal Pronouns in English Discourse - Bartkutė, Darija (Kalbotyra, 2005)
The present article is concerned with the determination and descriptive analysis of the basic patterns of intersentential anaphoric use of personal pronouns in J. Galsworthy’s The Man of Property. The purpose of this study is to examine the textual functions of personal pronouns drawing upon the theoretical assumptions of the science of text linguistics. The complexity of the relationship between the pronoun and its antecedent determines the distinction between simple and complex patterns of the intersentential anaphoric use of personal pronouns. Simple patterns serve the examination of the distances between the pronoun and the antecedent. The patterns in the given corpus demonstrate abundant instances of antecedent shifts which encumber the resolution process and thus allow us to consider the ambiguous relationships between the pronoun and the antecedent.